The handbook for investment committee members : how to make prudent investments for your organization - Olson, Russell L., 1933- (Wiley finance series., 2005)
Comprehensive coverage of what it takes to be a responsible member of an investment committeeIn a clear, organized, and easy-to-understand manner, this handbook explains the responsibilities and expectations of investment committee fiduciaries for pension funds, endowment funds, and foundations.